(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2019)
In the present work, bio-based polyol resin was prepared from the non-edible castor oil with reaction of diethanol amine. The prepared polyol was utilized in polyurethane synthesis by using different types of diisocynates. The spectral study of synthesized polyol was performed by FTIR. The prepared polyurethanes were coated on mild steel panel and glass plate. The coating properties such as gloss, corrosion, electrochemical, mechanical properties were performed on mild steel plates. While coating films were obtained by peeling out from glass plates. TGA of coated films was performed for their thermal stability.